Antipyretic Plants in Kasik Putih Timur Hamlet Cubadak Air Utara Village Pariaman Utara District Pariaman City - Delvia Suarman (Jurnal Serambi Biologi, 2023)
The use of plants as medicine has been carried out by Indonesian people for a long time, one of which is using plants to reduce body temperature or as antipyretics. The content of Flavonoid compounds in plants is efficacious for lowering body temperature. This study aims to determine the types of plants that can be used by the community as antipyretic drugs. The research method used is explorative which is qualitative in nature. Data collection was carried out through interviews with respondents. Respondents who were used to find out the types of plants as antipyretics were people who had knowledge and still used plants to treat diseases. Identification of plants is done by using related books and journals. Data analysis was carried out descriptively on the types of plants that have antipyretic properties. Based on the research results, it was found that 7 types of plants have antipyretic properties used by the people of East Kasik Putih Hamlet, Cubadak Air Utara Village, North Pariaman District, Pariaman City. The plants used are Annona muricata L. (Soursop), Kalanchoe pinnata L. (Sidinding), Jatropha curcas L. (Jirak), Hibiscus rosasinensis (Bungo Rayo), Abelmoschus manihot L. (Paracetamol), Nephelium Lappaceum L. (Rambutan) , Peronema canescens Jack (Sungkai). Key words Plants, Antipyretics, Kasik Putih Timur Hamlet